Association of a pace of aging epigenetic clock with rate of cognitive decline in the Framingham Heart Study Offspring Cohort - Micah J. Savin; Haoyang Wang; Heming Pei; Allison E. Aiello; Stephanie Assuras; Avshalom Caspi; Terrie E. Moffitt; Peter A. Muenning; Calen P. Ryan; Baoyi Shi; Yaakov Stern; Karen Sugden; et al. (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract INTRODUCTION The geroscience hypothesis proposes systemic biological aging is a root cause of cognitive decline. METHODS We analyzed Framingham Heart Study Offspring Cohort data (n = 2296; 46% male; baseline age M = 62, SD = 9, range = 25–101 y). We measured cognitive decline across two decades of neuropsychological‐testing follow‐up. We measured pace of aging using the DunedinPACE epigenetic clock. Analysis tested if participants with faster DunedinPACE values experienced more rapid cognitive decline compared with those with slower DunedinPACE values. RESULTS Participants with faster DunedinPACE had poorer cognitive functioning at baseline and experienced more rapid cognitive decline over follow‐up. Results were robust to confounders and consistent across population strata. Findings were similar for the PhenoAge and GrimAge epigenetic clocks. DISCUSSION Faster pace of aging is a risk factor for preclinical cognitive decline. Metrics of biological aging may inform risk stratification in clinical trials and prognosis in patient care. Highlights Faster DunedinPACE is associated with preclinical cognitive aging. Higher baseline cognition was protective of DunedinPACE‐associated cognitive decline. The DunedinPACE association with cognitive decline explained a fourth of dementia risk.